Impact of COVID-19 on Pharmaceutical Care Services and the Role of Community Pharmacists: A Multi-Center Cross-Sectional Study in Ethiopia - Dawit Kumilachew Yimenu B. Pharm, MSc; Chilot Abiyu Demeke B. Pharm, MSc; Asmamaw Emagn Kasahun B. Pharm, MSc; Ebrahim Abdela Siraj B. Pharm; Adane Yehualaw Wendalem B. Pharm; Zegaye Agmassie Bazezew B. Pharm; Abebe Basazn Mekuria B. Pharm, MSc (SAGE Publishing, 2021)
Objectives The current study aimed at assessing the impact of COVID-19 on pharmaceutical care services and the role of community pharmacists. Methods A cross-sectional study was conducted from May 1st to June 7, 2020, on community pharmacies in Bahir Dar and Gondar cities, Ethiopia. Descriptive statistics and Chi-square test were conducted. A P-value of less than 0.05 was considered to declare statistical significance at a 95% Confidence interval (CI). Results A total of 101 community pharmacies were approached (one pharmacist per pharmacy), and 80 of them had completed the survey. From the total pharmacies, 78.8% of them had encountered a shortage of pharmaceutical products. Chi-square test revealed that there was a significant difference ( P  = 0.036) in the shortage of personal protection equipment between Gondar and Bahir Dar cities. Face mask 55 (77.4%) followed by hand glove 15 (21.1%) were the most commonly reported personal protective equipment's in short supply. Conclusion Strategies should be in place to improve the availability and affordability of various essential pharmaceuticals to mitigate the spread of the disease and prevent other complications.